(untitled) (Ra. Revista de Arquitectura, 2020)
Approaching some of the questions raised in the “Material Oriented Ontology” call such as the Aesthetics and Ethics of Sustainability, this paper augues that the action of Recycling Social Housing stands for a model of Social Regeneration. In 1995 the awarded movie ‘La Haine’ revealed to the world the daily turmoil in which lived the inhabitants of the grands-ensembles (French post-war social housing): unemployment, criminality and violence were some of their constant companions. Faced by the unmistakable reality, the state promptly held as responsibles the urbanistic and architectonic models, setting into motion a large demolition-reconstruction plan, that is still up to date. Since 2004, the architects Anne Lacaton and Jean-Philippe Vassal have been active opposers to this unfounded policy. Not only through writing, but also through their built work, they’ve shown that the grands-ensembles are passible of a second life. Taking as their prime ‘raw material’ the already built context, they’ve successively rescued the Modern Movement’s machine Ã habiter by bringing the transition spaces of the Palladian villa into each one of the inhabited apartments.